EKSISTENSI KONSTITUSIONAL KOMISI KEJAKSAAN SEBAGAI LEMBAGA NEGARA INDEPENDEN DALAM TEORI DAN PRAKTIK HUKUM INDONESIA - Riki Handoyo; Johannes Ronald Elyeser Roparulian Hutagalung; Tomson Situmeang (Jurnal Riset Multidisiplin Edukasi, 2026)
The constitutional existence of the Attorney Commission as an independent state institution has become an important issue in Indonesia’s constitutional system, especially after the amendments to the 1945 Constitution which strengthened the principles of checks and balances among state institutions. This article analyzes the theoretical foundation, position, authority, and implementation of the Attorney Commission’s supervisory function in Indonesian legal practice through comparative perspectives with oversight institutions in other countries. Using normative legal research methods with statutory and conceptual approaches, this study finds that although the Attorney Commission is not explicitly mentioned in the 1945 Constitution, its constitutional legitimacy is based on four fundamental theories: the theory of checks and balances, the concept of Independent Regulatory Agencies (IRAs), the concept of auxiliary state organs, and the theory of the rule of law. The position of the Attorney Commission as an independent institution faces several challenges, including structural dependence on the President, limited enforcement power of recommendations, and budget constraints. In practice, the Attorney Commission has shown significant achievements with a response rate of 86.63% to its recommendations in 2025, although there are still gaps between recommendations and follow-up actions. Through analysis of strategic cases and comparative studies with oversight models in other countries, this article recommends strengthening the constitutional existence of the Attorney Commission through arrangements in higher legal regulations, expanding authority with quasi-judicial powers, increasing institutional capacity, establishing regional representatives, strengthening internal-external coordination, enhancing public participation, and conducting periodic effectiveness evaluations with clear indicators and roadmap for implementation.